2017
DOI: 10.4238/gmr16019035
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the correlation between early postinfarction pyramidal tract Wallerian degeneration and nerve function recovery using diffusion tensor imaging

et al.

Abstract: ABSTRACT. This study aimed to evaluate the clinical significance of diffusion tensor imaging (DTI) in the early diagnosis of pyramidal tract Wallerian degeneration (WD) and assessment of neurological recovery following cerebral infarction. This study included 23 patients with acute cerebral infarction and 10 healthy adult controls. All participants underwent both magnetic resonance imaging (MRI) and DTI scans. DTI images were analyzed using the Functional MRI of the Brain Software Library to determine the regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Our research showed some effect of CORT administration on WMT after stroke; however, it is not clear whether this effect is strictly negative. Clinically, WMT reorganization and microstructure have been proven to be associated with cognitive decline and functional recovery after stroke [11][12][13]40,41]. Similar effects after stroke have been observed in patients experiencing chronic stress and elevated cortisol levels [16,21,42].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Our research showed some effect of CORT administration on WMT after stroke; however, it is not clear whether this effect is strictly negative. Clinically, WMT reorganization and microstructure have been proven to be associated with cognitive decline and functional recovery after stroke [11][12][13]40,41]. Similar effects after stroke have been observed in patients experiencing chronic stress and elevated cortisol levels [16,21,42].…”
Section: Discussionmentioning
confidence: 75%
“…The association between stroke and secondary Wallerian degeneration of white matter has been explored in a number of preclinical [2,[5][6][7][8] and clinical studies [9,10]. Neuroimaging studies suggest that these changes are associated with neurological deficits and poorer functional outcomes post-stroke [11][12][13]. A study by Jokinen et al (2005) found that WMT hyperintensities on T2 diffusion-weighted images could be used as independent predictors of post-stroke cognitive impairment and were associated with poor performance in tests of mental speed, executive function, memory, and visuospatial functions [13].…”
Section: Introductionmentioning
confidence: 99%
“…After ischemic stroke, nerve fibers disintegrate due to ischemia, hypoxia, and necrosis of the local tissue. In addition, axonal injury and demyelination occur in the remote intact tissue due to Wallerian degeneration (19, 20). Therefore, the integrity and number of nerve fibers decrease.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous studies (21, 22), our results showed that the TDI and FA values reduced in both the non-involved lower and upper parts of the IL CST during follow-up, indicating that the integrity and number of fibers reduced in both the proximal and distal parts of the remote non-involved IL CST. In addition to the changes in the infarct itself, the infarct lesion will cut off the nutritional supply and synaptic connection between the inferior nerve fibers and the upper cortex, leading to Wallerian degeneration of the inferior nerve fibers, which causes axonal and myelin sheath disintegration and nerve fiber atrophy (19, 20). These changes lead to a reduction in the TDI and FA values.…”
Section: Discussionmentioning
confidence: 99%
“…Waller nominated the fragmentation of myelin, which he mentioned to as "medulla", into discreteunits of different sizes. The disintegrated axons shaped droplets that could be stained, consequently allowing studies of the development of individual nerve fibers [2].…”
Section: Augustus Wallermentioning
confidence: 99%